Identifikasi Serangan Hama dan Penyakit Pada Anakan Meranti Tembaga (Shorea leprosula Miq.) di Areal Persemaian BPDAS-HL Kahayan: Identification Of Damaged Caused By Pests and Diseases On Meranti Tembaga (Shorea leprosula Miq..) Seedlings in the Nursery Area of BPDAS-HL Kahayan - Eritha Kristiana Firdara; Reni Rahmawati; Ajun Junaedi; Penyang Penyang; Rosdiana Rosdiana; Iva Novic Purba (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Meranti tembaga (Shorea leprosula Miq.) is a fast-growing tree species with high economic value and an important role in reforestation and industrial forest plantation development. However, the success of seedling cultivation is often constrained by pest and disease attacks that may reduce seedling quality. This study aims to identify the types of pests and diseases attacking meranti tembaga seedlings, as well as to analyze their frequency, intensity, and level of damage. The research was conducted at the Permanent Nursery of BPDAS-HL Kahayan, Central Kalimantan, using 600 seedlings aged approximately four months. The results revealed three major pests, namely the grasshopper (Valanga nigricornis), the Asian tramp snail (Bradybaena similaris), and the mini snail (Subulina octona), along with three leaf spot diseases caused by Pestalotia sp., Colletotrichum sp., and Curvularia sp.. Pest attacks reached a frequency of 13.32% with an intensity of 2.76%, while diseases reached 30% with an intensity of 6.67%. Overall, the damage level was categorized as mild. Preventive measures can be taken by regulating humidity, weeding, and managing plant spacing in the nursery.